MOTIVASI BERWIRA USAHA DI KALANGAN MAHASISWA: APLIKASI THEORY OF PLANNED BEHAVIOR - Yulius Koesworo; Siprianus S. Sina; B. Diana Nugeraheni (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
Entrepreneurship motivation plays important role in developing new business organization. This research addresses to test variable influence entrepreneurship among students in East Java.  It refers to the theory of planned behavior  modified by Segel et. al (2004)  that uses three dependent variables, they are perceived feasibility or self afficacy (SE), risk tolerence (TR) and net desirability of self employment (NDSE) to explain entreprenuership motivation.To test this assertions, sample used are 854 students from 10 universities in Surabaya, Malang and Jember. Then, hypothesis both partial and simultanious  variables, SE,TR and NDSE have positive relation to entrepreneurship motivation (MB) tested by regression and correlation analysis. As a result,  findings support hypotesis and have significant implication for the way in which we conceptualize entrepreneurship motivation.